STRATEGI MANAJEMEN INOVASI DALAM PENYELENGGARAAN PEMERINTAHAN DESA BANUA LAWAS UNTUK PENINGKATAN PELAYANAN PUBLIK - Muhammad Sunaryo (Jurnal Humaniora & Sosial Sains, 2025)
Management is essential for village governance. Villages often face challenges in human resources, natural resources, and finances. This study aims to determine how governance is implemented in Banua Lawas Village, Tabalong Regency. This study aims to analyze innovation management strategies in the governance of Banua Lawas Village, Banua Lawas District, Tabalong Regency, to improve the quality of public services. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The results indicate that digital technology-based innovation strategies, strengthening the capacity of village officials, and collaboration with the community are key to success in realizing responsive and transparent public services. Obstacles faced include limited human resources, budget, and resistance to change. This study also highlights the importance of innovation management in improving public services in villages. Recommendations are provided for strengthening innovation governance and program sustainability.